Development of halal assurance system for shoyu production - Tanaka, Darren; Kusnandar, Feri; Giriwono, Puspo Edi (IPB University, 2024)
Muslim population in Indonesia was predicted to reach 214 million by 2019, making it a lucrative market from a business perspective. Muslims have the right to obtain and consume halal food products. Food and beverages must be manufactured from raw halal materials and processed in a manner that retains halal status. For instance, shoyu, a Japanese soy sauce widely consumed by Indonesians, traditionally contains a mixture of wheat and soybean fermented in two stages. Non-halal soy sauce may contain brewery or khamr alcohol and pork-derived substances as flavoring ingredients. Therefore, halal assurance system (HAS) 23000 was developed by LPPOM MUI (Food, Drug and Cosmetic Research Institute of Indonesian Ulema Council) and aimed at ensuring a product is free from contamination by haram or najis. HAS development for halal shoyu product line at Kamada Soy Sauce Inc. included conducting a preliminary audit using the gap analysis method. The development was considered complete once all 11 principles of HAS 23000 had been fulfilled. A post-audit was then performed using the same gap analysis method to compare the conditions before and after development. Subsequently, a risk analysis using failure mode and effect analysis (FMEA) was performed based on audit results and brainstorming sessions with the company. Construction of a fishbone diagram was carried out using the calculated risk probability number during FMEA risk analysis.